The Effectiveness of Pyrethrum, Neem, Beauveria bassiana and Metarhizium anisopliae Against Brown Plant hopper (Nilaparvata lugens Stal.) - Agus Kardinan; Tri Eko Wahyono; Nurbetti Tarigan (Buletin Penelitian Tanaman Rempah dan Obat, 2019)
Brown plant hopper (Nilaparvata lugens Stal) is the main pest on rice cultivation.  Synthetic insecticides application had negative impact to the human health and environment. The research objective was aimed to examine the effectiveness of botanical (pyrethrum and neem) and bio-insecticides (Beauveria bassiana/Bb and Metarhizium anisopliae/Ma) against brown plant hopper. Research was conducted at Entomology Laboratory of Indonesian Spices and Medicinal Crops Research Institute, Bogor in 2017. Trial consisted of two activities: the effectiveness of botanical and bio-insecticides to brown plant hopper mortality and horizontal transmission of bio-insecticides on brown plant hoppers. Botanical pesticide tested was (1) pyrethrum I (5 ml.l-1 water ), (2) pyrethrum II (5 ml.l-1 water), (3) neem I (20 ml.l-1 water), (4) neem II (20 ml.l-1 water), (5) synthetic insecticide (2 ml.l-1 water) and (6) control.  Bio-insecticide treatments were (1) Bb (spraying, 2.5 ml/plant), (2) Bb (granule, 5 g/pot), (3) Ma (spraying, 2.5 ml/plant), (4) Ma (granule, 5 g/ pot) and (5) control.  Treatments of horizontal transmission was the ratio of infected : healthy brown plant hopper 1 : 10; 2 : 10; 3 : 10 and 4 : 10. Botanical insecticides were prospective to suppressing brown plant hopper population of 85-87 % (pyrethrum) and   60-70 % (neem).   B.  bassiana was able  to   suppress   brown   plant     hopper population (18.2%), better than   M. anisopliae (5.6 %). Biological insecticide application by contact (spraying) was better than applied in granules form.  Botanical insecticide application showed no horizontal transmission from infected to healthy insect. Botanical insecticide (pyrethrum and neem) was more prospective than bio-insecticide (B. bassiana and M. anisopliae) in controlling brown plant hopper.